ANALYSIS OF PHYSICAL AND MENTAL WORKLOAD OF WORKERS WITH CARDIOVASCULAR LOAD (CVL) AND BOURDON WIERSMA AT PT XYZ - Arafah Aminah Lubis; Mochamad Tutuk Safirin (Center for Study and Journal Management FTI UMI, 2023)
PT XYZ is a manufacturing company that produces fabricated components and machines for various heavy construction industries, but the well-known product is train components. PT XYZ has agreed to export train components to many countries so that PT XYZ has a large production target. Workers must work on requests for goods according to a predetermined date, which can cause fatigue. Based on these problems, this research was conducted to determine the value of the physical and mental workload of shift 1 and shift 2 PT XYZ workers and provide suggestions for improvement. Cardiovascular Load (CVL) and Bourdon Wiersma methods are used to identify the worker's workload. Based on the research results, it is known that the workload of shift 2 workers is heavier than shift 1 workers. This problem can be influenced by working hours at night which are less optimal for work. Improvements suggested to overcome this include increasing rest time, setting up a shift system or rolling shifts, and improving the workplace.